Situation analysis on South African animal medicines, animal health and animal residues in foodstuffs - Molefe, S.M.; McCrindle, C.M.E.; Botha, C.J.; Makita, K.; Grace, Delia (2011)
The South African food safety and animal food control systems are developed and enforced by three government departments: Department of Health (DOH), Department of Agriculture, Forestry and Fisheries (DAFF) and Department of Trade and Industry (DTI). Animal health relies heavily on veterinary drugs for controlling pests and diseases. Movement of animals and animal products, is also a potential method of transmission of pests and diseases within and between countries. Human health is inextricably linked to animal health and production through zoonotic and foodborne hazards. By eating animal products (meat, milk, eggs, etc.), humans are exposed to microbiological hazards and chemical residues.This paper will describe and critically review the relevant legislation and regulations as well as their implementation, highlighting discrepancies and overlaps. Four working groups of eight key informants performed a gap analysis and defined actions and steps to remedy the gaps for: 1) Legislation for the registration for veterinary drugs and pesticides in animal feeds; 2) Animal health legislation, including veterinary public health, biosecurity and animal diseases; 3) Microbiological hazards and chemical residues in food of animal origin; and 4) Laboratory capacity for residues and animal diseases surveillance and monitoring. There is a shortage of academic institutions devoted to teach applied regulatory toxicology and aquatic animal health. Furthermore, due to duplication of activities from two authorities regulating the registration of veterinary medicines and stock remedies, there is poor utilization of scare skills for surveillance, monitoring and evaluators responsible for human food safety evaluation of drugs intended for food animals. Food safety of animal products is fragmented as a result of it not being under only one Ministry. Different aspects of legislations fall under the three departments. Lines of responsibility are not always well understood as they sometimes overlap and inconsistently applied. There are also a number of stakeholders involved at local, regional and international level. International standards in line with Codex, World Trade Organization (WTO) and the World Organisation for Animal Health (OIE), are followed, in line with international obligations. National governments and private sector standards are applied by producers and processors of animal derived food. At local level there are provincial and municipal regulations for implementation of National directives, as well as private standards of supermarkets, butchers, dairies and other retailers of animal derived foods. In conclusion, South Africa needs to have one broad veterinary legislation which covers animal disease control, registration and control of veterinary drugs (including insecticides manufactured for administration to animals), food safety including food protection, prevention and elimination of zoonoses and aspects of laboratory animal facilities and diagnostic laboratories, health education and extension.